A randomized countermeasure against parasitic adversaries in wireless sensor networks - Luo, Jun. (2011)
Due to their limited capabilities, wireless sensor nodes are subject to physical attacks that are hard to defend against. In this paper, we first identify a typical attacker, called parasitic adversary, who seeks to exploit sensor networks by obtaining measurements in an unauthorized way. As a countermeasure, we first employ a randomized key refreshing: with low communication cost, it aims at confining (but not eliminating) the effects of the adversary. Moreover, our low-complexity solution, GossiCrypt, leverages on the large scale of sensor networks to protect data confidentiality, efficiently and effectively. GossiCrypt applies symmetric key encryption to data at their source nodes; and it applies re-encryption at a randomly chosen subset of nodes en route to the sink. The combination of randomized key refreshing and GossiCrypt protects data confidentiality with a probability of almost 1; we show this analytically and with simulations. In addition, the energy consumption of GossiCrypt is lower than a public-key based solution by several orders of magnitude.